is it possible the effective realization via court of economic, social and cultural rights? - Higuera Licona, Gabriel (Universidad Autónoma de Tamaulipas, 2019)
The current democratic states with guaranteed rule of law find the basis of their action in the humanistic ideas of human rights, which in their progression seek to meet even the most important needs of the people or, at least, its vital minimum. Notwithstanding the road to its effective realization, this barely begins and does not have an easy route. It is not enough to insist on it even by judicial means, if the original civil and political rights have not reached its full development. As well, from the progressive party estimated that minimum content should find a protect, it should explore creative forms of the use of existing resources, which is very reasonable, but should not be left aside the realistic positions closely related to the economic phenomenon.